The Dominicans and the Making of Florentine Cultural Identity (13th-14th centuries) / I domenicani e la costruzione dell'identità culturale fiorentina (XIII-XIV secolo) - Bartuschat, Johannes (Reti Medievali e-book, 2020)
Florence, the celebrated city-republic, dominates the historiography of medieval Italy still today. The birth and growth of the Mendicant Orders paralleled the rise of urban Europe. As attention to medieval cities has increased, so too the history of the Dominican Order has constituted a major field of study, since the Dominicans were at the forefront of the cultural and religious life of Medieval cities. The combination of these two traditions of studies precipitates a particularly fruitful research field: the reciprocal influences and interactions between the activities of Dominican intellectuals and the making of Florentine cultural identity. The essays collected in this volume explore various facets of such an interaction. Without presuming to be exhaustive, these contributions restore the complexity of the relationship between the Dominicans and the city of Florence as well as the communal society in the broadest sense of the term.